Coping With Negative Emotions in Purchase‐Related Situations - Yi, Sunghwan; Baumgartner, Hans (Journal of Consumer Psychology, 2004)
We investigate how consumers manage stressful emotional experiences in purchase‐related situations. Eight coping strategies that consumers may use to deal with stressful incidents are distinguished and hypotheses are formulated about which coping strategies are linked to each of four different negative emotions (anger, disappointment, regret, and worry). The findings indicate that distinct strategies are employed by consumers to cope with different emotions, or the problem that caused these emotions, and that the emotion‐coping relations are generalizable across two samples of respondents.